Geographic and facility variation in initial use of non-tunneled catheters for incident maintenance hemodialysis patients. Issue 1 (December 2016) - Clark, Edward; Akbari, Ayub; Hiebert, Brett; Hiremath, Swapnil; Komenda, Paul; Lok, Charmaine; Moist, Louise; Schachter, Michael; Tangri, Navdeep; Sood, Manish
Abstract Background Non-tunneled (temporary) hemodialysis catheters (NTHCs) are the least-optimal initial vascular access for incident maintenance hemodialysis patients yet little is known about factors associated with NTHC use in this context. We sought to determine factors associated with NTHC use and examine regional and facility-level variation in NTHC use for incident maintenance hemodialysis patients. Methods We analyzed registry data collected between January 2001 and December 2010 from 61 dialysis facilities within 12 geographic regions in Canada. Multi-level models and intra-class correlation coefficients were used to evaluate variation in NTHC use as initial hemodialysis access across facilities and geographic regions. Facility and patient characteristics associated with the lowest and highest quartiles of NTHC use were compared. Results During the study period, 21, 052 patients initiated maintenance hemodialysis using a central venous catheter (CVC). This included 10, 183 patients (48.3 %) in whom the initial CVC was a NTHC, as opposed to a tunneled CVC. Crude variation in NTHC use across facilities ranged from 3.7 to 99.4 % and across geographic regions from 32.4 to 85.1 %. In an adjusted multi-level logistic regression model, the proportion of total variation in NTHC use explained by facility-level and regional variation was 40.0 % and 34.1 %, respectively. Similar results were observed for the subgroup of patients who received greater than 12 months of pre-dialysis nephrology care. Patient-level factors associated with increased NTHC use were male gender, history of angina, pulmonary edema, COPD, hypertension, increasing distance from dialysis facility, higher serum phosphate, lower serum albumin and later calendar year. Conclusions There is wide variation in NTHC use as initial vascular access for incident maintenance hemodialysis patients across facilities and geographic regions in Canada. Identifying modifiable factors that explain this variation could facilitate a reduction of NTHC use in favor of more optimal initial vascular access.